Utopianism, insurgency and urban space: Lefebvre’s “right to the city” and the June 2013 Journeys in Brazil - Santos, Gustavo Souza; Pereira, Anete Marília (Pontifícia Universidade Católica de São Paulo, 2019)
The metropolis of São Paulo was the stage and epicenter for the volatile, spontaneous, diffused and reticulated odyssey that characterized the June 2013 Journeys in Brazil. The urban space has become an index and a platform to struggle for social dreams. In this article, we reflect on the association between this mobilization and the “right to the city” in a perspective of utopianism about the urban space, based on the being and on socio-political action. As a contribution to this study, we analyzed the news content of the printed newspapers with the highest circulation in the period, audited by the Communication Verification Institute (IVC). The movement revealed projects of life and country mobilized in the appropriation of the urban space for struggle in a utopian flexion, as a social-spatial sign of insurgency and social development.